2005
DOI: 10.1016/j.jacc.2005.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Artery Surgery for Reducing Mortality and Morbidity

Abstract: Randomized controlled trials did not find, aside from atrial fibrillation, the statistically significant reductions in short-term mortality and morbidity demonstrated by observational studies. These discrepancies might be due to differing patient-selection and study methodology. Future studies must focus on improving research methodology, recruiting high-risk patients, and collecting long-term data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
158
1
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(177 citation statements)
references
References 75 publications
7
158
1
11
Order By: Relevance
“…However, our results support the findings of a recent meta-analysis of risk adjusted observational studies 23 favouring the OPCAB technique for stroke reduction. To assess patient consciousness status we utilized the NEECHAM confusion scale which has been shown to reflect clinical impact of cerebral embolic load and new DW-MRI lesions after ONCAB surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results support the findings of a recent meta-analysis of risk adjusted observational studies 23 favouring the OPCAB technique for stroke reduction. To assess patient consciousness status we utilized the NEECHAM confusion scale which has been shown to reflect clinical impact of cerebral embolic load and new DW-MRI lesions after ONCAB surgery.…”
Section: Discussionsupporting
confidence: 90%
“…However, the OPCAB technique was associated with significant reduction in stroke in a meta-analysis of 22 risk-adjusted observational studies evaluating patients at high risk for neurological injury. 23 It was likely that lower stroke rates after OPCAB surgery were secondary to less aortic manipulation and reduced cerebral embolic load in patients with atheromatous aorta. [24][25][26] The discrepancies between the RCTs and risk-adjusted observational studies may be attributed to different patient populations being studied, i.e., the RCTs are usually associated with recruitment of low-risk patients whilst the observational studies better reflect patient diversity similar to that of clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A larger observational study by Williams et al (27) also demonstrated an increased risk for repeat revascularization with OPCAB surgery (RR 1.29, P=0.02). Other studies (23,27,28) have reported similar increased need for early revascularization following OPCAB. The increased need for repeat revascularization may outweigh any potential economic benefits of earlier intensive care unit and hospital discharge.…”
Section: Discussionmentioning
confidence: 65%
“…Ascione and Angelini (5) discussed the dilemma faced by many cardiac surgeons who perform CABG. On one hand, the literature is replete with studies that emphasize the potential for reducing postoperative morbidity and length of stay with OPCAB surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); on the other hand, there is continued concern regarding intraoperative myocardial ischemia, inadequate revascularization and the need for early revascularization (5,8,23,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Two meta-analyses demonstrated a reduction in mortality at 30 days, in off-pump surgery technique, but also there were less grafts, and more late reinterventions were required [3][4][5][6] . The difference between offpump surgery and traditional technique in the number of grafts and late patency rates, which had been observed in previous studies, was not confirmed by subsequent studies, since no statistically significant difference was demonstrated 7 .…”
mentioning
confidence: 99%